El Diccionario Tecnológico Hispano-Americano, Un Nuevo Intento en la Institucionalización de la Lengua de la Ciencia y de la Técnica en Español. (3rd June 2014) - Garriga Escribano, Cecilio; Pardo Herrero, Pilar
Abstract: The Diccionario Tecnológico Hispano-Americano, a new attempt at institutionalizing the language of science and technology in Spanish. The Diccionario Tecnológico Hispano-Americano (1926-1931) is a very important work in the history of Spanish lexicography, even though its publication was suspended shortly after it was begun, because it is an attempt to establish a panhispanic guideline for scientific and technical vocabulary. Initially, the project received major support from institutions and intellectuals, as it responded to the shared interests of technicians and philologists. In this paper some important aspects about the DTHA are dealt with, such as the precedents that gave rise to the project, the starting point of the dictionary, the circumstances of its production, and the reasons that led to the work being halted. In addition, technical characteristics of the dictionary (macro- and microstructure) are analyzed, some sources are revealed and the possible influence in the way of dealing with scientific and technical terms by later dictionaries of the 20th century is confirmed.